Improved thermal and mechanical properties of polynorbornene upon covalent attachment with graphene sheets. (11th August 2017) - Mukherjee, Madhumita; Mukherjee, Saikat; Kumar, Rajan; Shunmugam, Raja
Abstract: Graphene carboxylic acid based polynorbornene nanocomposites were fabricated following simple synthetic protocol with different graphene loading. Polynorbornene (PNDA ) was functionalized with hexamethylene diamine modified graphene carboxylic acid (HXNG ) to form new hybrids:PNDHXNG1-3 . Formation of monomer (NDA ) andPNDA were confirmed by standard analytical techniques. Covalent attachment betweenPNDA andHXNG was confirmed by IR, Raman and PXRD. Hybrids exhibited excellent solubility in DCM:MeOH (2:1). Increased thermal stability and enhanced value of Tg of the hybrids, as compared toPNDA was evidenced from TGA, DTG, DTA and DMTA analysis. 69% increment in storage modulus was achieved in case ofPNDHXNG3 . Almost 97%, 73% and 181% increment were observed in yield stress, stress at break and Young's modulus respectively in case ofPNDHXNG3 . Improved thermal and mechanical properties were observed with increasingHXNG loading inPNDHXNG1-3 . Morphological studies revealed excellent miscibility betweenHXNG andPNDA inPNDHXNG s owing to improved thermal and mechanical properties. Graphical abstract: